Analysis of Islamic Criminal Law on Continued Criminal Acts by Children - Syafiq, Syafiq Aljani Siagian; Imam Yazid (KRTHA BHAYANGKARA, 2025)
The handling of ongoing sexual violence crimes committed by children requires an approach that considers victim protection, offender rehabilitation, and legal certainty. Using Decision Number 59/Pid.Sus-Anak/2024/PT MDN as a framework, this essay examines how Islamic criminal law applies to persistent cases involving juvenile offenders.  Researchers used primary and secondary sources, conducted descriptive and qualitative analyses, and adhered to a normative juridical methodology that included a statute approach, a case approach, and an examination of Islamic law. The results show that the judges' decision to impose a 12-month prison term with a 6-month work-study program was based on legal considerations (Article 81 paragraph (2) of Law No. 17/2016 Jo. Article 64 paragraph (2) of the Criminal Code Jo. Law No. 11/2012), philosophical considerations (the rehabilitation of children), and sociological aspects (the psychological impact on victims). According to Islamic criminal law, a juvenile offender who commits a crime at the age of seventeen is regarded to be in the puberty and accountability stages, but due to the presence of compulsion and the juvenile's position, syubhat (doubt) arises, and hudud is not enforced.  In accordance with the concepts of ishlah (reform) and ta'dib (education), the crime is designated as jarimah zina (fornication) with violent components and is punished with ta'zir, a kind of education that is both corrective and instructional.  Islamic law and positive law work together to prioritize victim protection and offender rehabilitation, as emphasized by this ruling, which represents maqasid syariah, especially hifz al-nafs (protection of life) and hifz al-nasl.